Statistical characteristics for directional wind speed for design building structure - Nuraziatul, Najwa Rosli (2019)
The wind hazard due to the windstorm had caused many damaged to the building or structure. The building or structure tends to collapse due to the non-durability of building in facing the windstorm that comes from many directions. Current records showed that most of the building failed to withstand the windstorm as the design method does not considering the wind direction effect especially for the high rise building [ 1]. Most of the high rise building failed to withstand the major directional of wind speed due to the lack of proper well design of building. However, in this study, it is more focus in investigating the wind characteristics for design purpose. Therefore, the wind speed probability and wind direction should be known in order to propose the design considering wind load characteristics. The wind speed data used in this study is obtained from the Malaysian Meteorological Department (MMD) of five specified locations. The wind speed probability was analysed by using the statistical method in order to know the wind speed statistical analysis. From the result, the orientation of directional wind speed can be identified based on the specific location. The result also shows that each location has their major directional wind speed with different type of terrain and topography. Therefore, these data can give guideline to the designer in design the building in withstand the high wind speed and reduce the wind hazard damages in Malaysia.